Evaluation of mechanical properties and corrosion resistance in stainless steel model 25Cr 6Mo 5Ni alloy with and without Boron addition - Francisco Evaristo UchÃa Reis (2015)
Superferritic stainless steels are widely used in heat exchangers and in petrochemical power plant because of their excellent mechanical properties coupled to corrosion resistance in chloride rich environments. In this research new superferritic alloys with high Cr, Mo, and Ni contents were produced for oil industry applications. Therefore, two superferritic stainless steels model alloys were developed, one with 0.07% B addition and another one without this alloying element. The phase diagrams for both materials were carried out by Thermo-Calc computacional program. Microstructure characterization was performed using the following techniques: optical and scanning electron microscopy, energy-dispersive spectroscopy, and Xray diffraction. The mechanical properties were assessed by hardness measurements, Charpy impacts and tensile tests. Corrosion resistance of the model alloys in aqueous solution 0.6 M NaCl was investigated by open circuit potential, potentiodynamic cyclic anodic polarization, and electrochemical impedance spectroscopy. Furthermore, critical pitting temperature was determined. The results showed that the superferritic stainless steel model alloy without B addition achieved better mechanical properties than the one of the two commercial superferritic stainless steels alloys. The corrosion resistance of this alloy was similar to the one of the superaustenitic stainless steels, and superduplex in aqueous solution 0.6 M NaCl. However, there was the formation of eutectoid lamellar constituent like perlite for the superferritic stainless steel model alloy with B addition. This eutectoid constituent was deleterious to mechanical properties, as well as to corrosion resistance for the material developed and studied in this thesis.